The coupled spatiotemporal evolution of glacier snow line altitude and flow velocity at the early 21st century in the Qilian Mountains - Qibing Zhang; Wei Chen (European Journal of Remote Sensing)
Glaciers serve as sensitive indicators of climate change, with their dynamics significantly impacting regional water resources and global sea level rise. This study investigates the spatiotemporal evolution of glacier snow line altitude (SLA) and flow velocity in the Qilian Mountains during the early 21st century using remote sensing data. Results indicate a rising trend in SLA across both the western and central Qilian Mountains, with the central region exhibiting a higher rate of increase (11.2 m yr−1) compared to the western region (5.99 m yr−1). Concurrently, glacier flow velocities decelerated in both regions at similar rates (0.04 m yr−1 and 0.03 m yr−1, respectively). Glacier thinning observed since 2000, coupled with rising SLAs and decreasing velocities, collectively reflect a negative mass balance. Regional climate analysis reveals pronounced temperature increases (0.26–0.45°C per decade) and modest precipitation gains, aligning spatially with glacier retreat patterns. Overall, the observed changes in glacier behavior reflect the strong influence of ongoing climate change in the Qilian Mountain region.